Freedom, Self-Prediction, and the Possibility of Time Travel - Fernandes, Alison (My University, 2020)
Do time travellers retain their normal freedom and abilities when they travel back in time? Lewis, Horwich and Sider argue that they do. Time-travelling Tim can kill his young grandfather, his younger self, or whomever else he pleases—and so, it seems can reasonably deliberate about whether to do these things. He might not succeed. But he is still just as free as a non-time traveller. I’ll disagree. The freedom of time travellers is limited by a rational constraint. Tim can’t reasonably deliberate on killing his grandfather, certain that he’ll fail. If Tim follows his evidence, and appropriately self-predicts, he will be certain he won’t kill his grandfather. So if Tim is both evidentially and deliberatively rational, he can’t deliberate on killing his grandfather. This result has consequences. Firstly, it shows how evidential limits in the actual world contribute to our conception of the future as open. Secondly, it undercuts arguments against the possibility of time travel. Thirdly, it affects how we evaluate counterfactuals in time travel worlds, as well as our own. I’ll use the constraint to motivate an evidential and temporally neutral method of evaluating counterfactuals that holds fixed what a relevant deliberating agent has evidence of, independently of her decision. Using this method, an agent’s local abilities may be affected by what happens globally at other times, including the future.
PUBLISHED
Keywords: Time Travel; Freedom; Deliberation; Causation; Counterfactuals; Time asymmetry; Creative Arts Practice; Freedom; Time Travel